Features of traditional folk Ukrainian decorative painting and its visualization in modern conditions - Omelchenko, Olga (Professional Art Education, 2023)
Object. The article examines and analyzes the artistic features of folk Ukrainian home painting, the factors of its emergence, the content of artistic conception, techniques of execution and development. Methods & methodology. During the scientific research, the methods of literary and scientific review, historical and comparative synthesis, and analysis of author’s artistic works were used. The scientific novelty consists in the search, concretization and systematization of historical assets in the content of traditional folk Ukrainian decorative painting with the aim of their use, transfiguration into today’s practice. Results. Special attention is focused on preserving the traditions of decorating the home with symbolic motifs - charms that originated in the beliefs of pagan times, continued to exist in Christianity and have reached modern times. A characteristic feature of folk art is syncretism, where the "World Order" was reproduced on functional everyday objects by means of ornamental compositions. The variability of the artistic language of home painting, its influence on the creation of new types of folk graphic art at the beginning of the 20th century is noted. The role of gifted artists in creating centers, schools and industries in different regions of the country is emphasized. The creative searches of modern masters and their examples of connections between folk art and the present are considered. A common feature of the preservation and development of folk art is the family traditions of artists of different generations who continue and develop their own abilities in decorative painting, painting of public interiors and household products, clothing design, textiles, graphic design, and souvenir products. Conclusions. On the example of the analysis of traditional home painting in the 20th century in different regions of Ukraine, the types of folk graphics, naive art, easel graphics, monumental and decorative painting, applied art, etc. are considered. It has been proven that today there are a large number of stylistic directions of environmental shaping, graphic design, clothing, textiles, furniture: classic, historical, futuristic, ethnic, etc. Those artists who choose folk art as a source of inspiration or conceptual direction seek, first, to preserve traditional culture, historical spirituality; secondly, to find individual creative connections of the past and the present.